2008
DOI: 10.1016/j.chom.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Virulence Is Mediated by PtpA Dephosphorylation of Human Vacuolar Protein Sorting 33B

Abstract: Entry into host macrophages and evasion of intracellular destruction mechanisms, including phagosome-lysosome fusion, are critical elements of Mycobacterium tuberculosis (Mtb) pathogenesis. To achieve this, the Mtb genome encodes several proteins that modify host signaling pathways. PtpA, a low-molecular weight tyrosine phosphatase, is a secreted Mtb protein of unknown function. The lack of tyrosine kinases in the Mtb genome suggests that PtpA may modulate host tyrosine phosphorylated protein(s). We report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
281
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(292 citation statements)
references
References 26 publications
10
281
0
1
Order By: Relevance
“…Several effector proteins from pathogenic bacteria were shown to mimick host proteins such as phosphatases or kinases to evade host immune defenses (33,35,(49)(50)(51). Because Mce3E has a DEF motif and could interact with ERK1/2 directly, we initially examined whether Mce3E could be able to dephosphorylate p-ERK directly, but we were not able to demonstrate the phosphatase activity of Mce3E toward p-ERK in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Several effector proteins from pathogenic bacteria were shown to mimick host proteins such as phosphatases or kinases to evade host immune defenses (33,35,(49)(50)(51). Because Mce3E has a DEF motif and could interact with ERK1/2 directly, we initially examined whether Mce3E could be able to dephosphorylate p-ERK directly, but we were not able to demonstrate the phosphatase activity of Mce3E toward p-ERK in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…After phagocytosis, Mtb blocks phagosome acidification as well acquisition of hydrolytic enzymes and anti‐microbial peptides. Two major Mtb virulence factors are involved in the blockage of the phagosomal maturation in human cell lines: the glycolipid lipoarabinomannan (LAM) (Hmama et al ., 2004; Kang et al ., 2005; Welin et al ., 2008) and the secreted tyrosine phosphatase (PtpA) (Bach et al ., 2008; Wong et al ., 2011; Wong and Jacobs, 2011). Mtb lacking the surface lipid trehalose dimycolate (TDM) failed to block phagosome maturation in mouse macrophages (Katti et al ., 2008) but to date, this has not been shown in human cells.…”
Section: Cell Autonomous Defence Mechanisms In Tbmentioning
confidence: 99%
“…We have previously shown that the low molecular weight tyrosine phosphatase, PtpA, is needed to block phagosome maturation and is essential for M. tuberculosis pathogenicity within human macrophages (8). PtpA's substrate in the host is the human vesicle trafficking protein vacuolar protein sorting 33B (hVPS33B) (8,9), which plays a key role in the regulation of membrane fusion in the endocytic pathway (10).…”
mentioning
confidence: 99%
“…PtpA's substrate in the host is the human vesicle trafficking protein vacuolar protein sorting 33B (hVPS33B) (8,9), which plays a key role in the regulation of membrane fusion in the endocytic pathway (10). Dephosphorylation of hVPS33B by PtpA translates directly into phagosome maturation arrest (8).…”
mentioning
confidence: 99%